2003
DOI: 10.1111/j.1365-3083.2003.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Heat‐Shock Protein 70 Levels in Patients with Acute Infection: Use of an Optimized Enzyme‐Linked Immunosorbent Assay

Abstract: Heat-shock proteins (Hsps) are highly conserved throughout evolution and evoke great interest both in basic biology and in medicine. They are expressed in small quantities under normal conditions, and their expression can be strongly induced by several stressors. Although their action is basically intracellular, it is now obvious that these proteins can be released into the extracellular environment from viable cells. In this study, the human Hsp 70 serum concentrations were determined using an optimized, cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 54 publications
2
60
1
2
Order By: Relevance
“…Baseline levels of HSP-70 were generally higher (mean, 4.9 ng/ml) in this group than in the patients receiving biopsies (<1 ng/ml). Studies using a manufactured ELISA test generally report a significant variation of HSP-70 serum level in healthy donors ranging from less than 1 up to 14 ng/ml (Abe et al 2004;Adewoye et al 2005;Fehrenbach et al 2005;Genth-Zotz et al 2004;Molvarec et al 2007;Njemini et al 2003;Walsh et al 2001) and thus comparable to the levels that we found. Several physiological conditions may influence these levels, such as ageing (Rea et al 2001), pregnancy (Molvarec et al 2007) or physical exercise (Fehrenbach et al 2005;Walsh et al 2001).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Baseline levels of HSP-70 were generally higher (mean, 4.9 ng/ml) in this group than in the patients receiving biopsies (<1 ng/ml). Studies using a manufactured ELISA test generally report a significant variation of HSP-70 serum level in healthy donors ranging from less than 1 up to 14 ng/ml (Abe et al 2004;Adewoye et al 2005;Fehrenbach et al 2005;Genth-Zotz et al 2004;Molvarec et al 2007;Njemini et al 2003;Walsh et al 2001) and thus comparable to the levels that we found. Several physiological conditions may influence these levels, such as ageing (Rea et al 2001), pregnancy (Molvarec et al 2007) or physical exercise (Fehrenbach et al 2005;Walsh et al 2001).…”
Section: Discussionsupporting
confidence: 86%
“…HSP are abundantly expressed intracellularly, but have also been described at the cytoplasmic membrane of tumor or virally infected cells (Bolhassani and Rafati 2008). They are also found in the intercellular space under various physiological situations (Abe et al 2004;Nakajima et al 2009;Njemini et al 2003;Rea et al 2001), including cell necrosis (Basu et al 2000). One of the main functions of intracellular HSP is tissue protection against otherwise lethal injuries by induction of protective mechanisms including inhibition of apoptosis (Garrido et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of Hsp70 from a variety of cells in response to cellular stress has been widely reported. For example, it has been shown that Hsp70 is present in the sera of normal individuals and its circulating levels are related to the levels of inflammation markers (Chan et al, 1999;Dybdahl et al, 2002;Njemini et al, 2003Njemini et al, , 2004. Treatment of macrophages with oxidized low density lipoprotein significantly increased Hsp70 concentration in supernatants, compared with untreated control (Svensson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 has been known to act not only as an intracellular chaperon, but also as a secretory protein (Chan et al, 1999;Asea et al, 2000;Guzhova et al, 2001;Somersan et al, 2001;Dybdahl et al, 2002;Njemini et al, 2003;Hunter-Lavis et al, 2004;Kimura et al, 2004;Njemini et al, 2004). Secretion of Hsp70 from a variety of cells in response to cellular stress has been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hücre koruyucu fonksiyonları olduğu bilinmektedir ve gebe olmayan, sağlıklı bireylerde de periferal dolaşımda HSP70 saptanmıştır (2) . Periferal ve renal vasküler hastalıkta (3) , egzersiz ile (4) , akut enfeksiyonda (5) , konjestif kalp yetmezliğinde (6) , septik şokta (7) , cerrahi sonrası (8) ve myokard enfaktüsünde (9) periferal dolaşımaki HSP70 düzeyi-nin arttığı saptanmıştır.…”
Section: Introductionunclassified